Caracterização da resposta imune funcional induzida por antígenos recombinantes baseados na estrutura da proteína tbpB de haemophilus parasuis - Barasuol, Bibiana Martins (2016)
In this study, through in vitro assays, we present the functional characterization the antibody against transferrin binding protein B (TbpB) from Haemophilus parasuis. Four recombinant antigen-based on the protein structure of TbpB were developed and evaluated in this study. The intact TbpB protein (TbpB-I20-528aa, mutant TbpB TbpB-M26-528aa and subdomains (lobes) NTbpB-Nm 20-282aa mutant version) and C TbpB-C283-528aa of TbpB from H. parasuis, serotype 5, Nagasaki strain, were cloned into pET20 expression vector and expressed in cells of Escherichia coli, strain ER 2566. The recombinant antigens were purified by liquid chromatography. Pigs were immunized with recombinant antigens adjuvanted with the adjuvant Montanide IMS 2215 VG PR and, the kinetics of antibody response was assessed by indirect ELISA. The antisera capacity to recognize 6 virulent strains of H. parasuis (Nº4 – Serovar (SV) 1, SW124 – SV4, Nagasaki – SV5, H425 – SV12, 84-22113 – SV14 e 84-15995 – SV15) was analyzed by flow cytometry, as well as the effect of antibodies opsonization during the H. parasuis phagocytosis performed by swine neutrophils. Finally, we analyze the ability of different antisera to activate the classical pathway of the complement system and to produce the killing of bacteria through antibody-mediated bactericidal assay. The results presented in this study demonstrate that all recombinant antigens were immunogenic in pigs and, that higher titres of antibodies were induced by antigens TbpB-M and TbpB-C, respectively. Except for SV4, all others serovars (SV1, SV5, SV12, SV14 e SV15) were strongly recognized (60-90%) by one or more specific antisera, demonstrating that TbpB protein from 6 virulent serovars analyzed share conserved epitopes in both lobes, N and C of the TbpB protein. In general, the number of antibodies associated with the strains was lower when we used the antisera produced with TbpB-I antigen. Interestingly, we observed that the homogenous expression of native TbpB protein from H. parasuis (independently of serovar) is only achieved if the microorganism is growth in iron starvation. Regarding the phagocytosis, we observed that the opsonization process, independently of the specific type of antibody, have increased the number of neutrophils with associated bacteria, as well, the number of bacteria captured by each neutrophil. The percentage of neutrophils with internalized bacteria was significantly higher when the microorganism was opsonized, however, this process seems to be slower against the SV12. Surprisingly, none of the swine antisera was capable of activating the classical pathway of the complement system (CPCS), suggesting that the Montanide IMS 2215 VG adjuvant has induced an antibody isotype with reduced functional activity in pigs. On the other hand, antibodies produced in mice against the TbpB-M, TbpB-Nm and TbpB-C protein adjuvanted with Freund adjuvant and/or Montanide Gel 01 were able to activate CPCS against all sevorars included. In summary, we demonstrate in this study, the functional activity of specific antibodies generated against four recombinant antigens based on the structure of TbpB protein from H. parasuis. The results presented are useful to predict in vitro the capacity of homologous and heterologous protection of vaccines based on these antigens.